Natural History of Disseminated Coccidioidomycosis: Examination of the Veterans Affairs–Armed Forces Database. (11th August 2020) - Bays, Derek J; Thompson, George R; Reef, Susan; Snyder, Linda; Freifeld, Alana J; Huppert, Milt; Salkin, David; Wilson, Machelle D; Galgiani, John N
Abstract: Background: The natural history of non–central nervous system (non-CNS) disseminated coccidioidomycosis (DCM) has not been previously characterized. The historical Veterans Affairs (VA)–Armed Forces coccidioidomycosis patient group provides a unique cohort of patients not treated with standard antifungal therapy, allowing for characterization of the natural history of coccidioidomycosis. Methods: We conducted a retrospective study of 531 VA–Armed Forces coccidioidomycosis patients diagnosed between 1955–1958 and followed to 1966. Groups were identified as non-DCM (462 patients), DCM (44 patients), and CNS (25 patients). The duration of the initial infection, fate of the primary infection, all-cause mortality, and mortality secondary to coccidioidomycosis were assessed and compared between groups. Results: Mortality due to coccidioidomycosis at the last known follow-up was significantly different across the groups: 0.65% in the non-DCM group, 25% in the DCM group, and 88% in the CNS group ( P < .001). The primary fate of pulmonary infection demonstrated key differences, with pulmonary nodules observed in 39.61% of the non-DCM group, 13.64% of the DCM group, and 20% of the CNS group ( P < .001). There were differences in cavity formation, with 34.20% in the non-DCM group, 9.09% in the DCM group, and 8% in the CNS group ( P < .001). Dissemination was the presenting manifestation or was concurrent with the initial infection in 41% and 56% of patients in the non-CNS DCM and CNS groups, respectively. Conclusions: This large, retrospective cohort study helps characterize the natural history of DCM, provides insight into the host immunologic response, and has direct clinical implications for the management and follow-up of patients. Abstract : This large, retrospective cohort study helps characterize the natural history and mortality of disseminated coccidioidomycosis, provides insight into the host immunologic response, and has direct clinical implications for the management and follow-up of patients.